Analisis Disiplin Belajar dan Minat Belajar dengan Hasil Belajar Matematika di Masa Pandemi Covid-19 - Anis Azizah; Nyoman Sridana; Arjudin Arjudin; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research aims to describe learning discipline, interest in learning and students’ mathematics learning during the covid-19 pandemic and to know presence or absence of a relationship between learning discipline and interest in learning with mathematics learning during the covid-19 pandemic on students grade XI IPS SMA Negeri 8 Mataram even semester in the academic year 2019/2020. This research is an ex post facto research. The population of this research were all students grade XI IPS SMA Negeri 8 Mataram is 194 students. While the sample was taken with a proporsional cluster random sampling technique is 66 students. The data was collected by using learning discipline questionnaire, interest in learning questionnaire, mathematics learning test, and interview. Based on the results of data analysis, it was found that the level of learning discipline of students in the very high category, interest in learning in the high category, and learning outcomes in the low category. The result of the study also showed that there was no relationship between learning discipline and interest in learning with mathematics learning during the covid-19 pandemic on students grade XI IPS SMA Negeri 8 Mataram even semester in the academic year 2019/2020, either individually or together.